The aspects of information and communication technology in the educational system of Islam- comprehensive review - Shaikh, Amina; Zeki, Akram M.; Shah, Asadullah (UiTM Press, 2023)
The advancement of teaching and learning across the majority of courses is made possible by information and communication technology (ICT), and Islamic studies is no exception. Education has been among the many industries that information and communication technology (ICT) has revolutionized. Islamic education has embraced ICT to improve teaching and learning processes since it is based on the Quran's teachings and the traditions of the Prophet Muhammad (peace be upon him). This article aims to address the role of digital technology, or ICT, in Islamic teaching and learning, as well as ICT applications for spreading Islamic education, which are becoming increasingly significant over time. Overall, this review offers insightful information about the state of ICT integration in Islamic education today and shows the upcoming directions for additional study and advancement in this area.